2022
DOI: 10.1002/jso.26784
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned and keys to success: Provider experiences during the implementation of virtual oncology tumor boards in the era of COVID‐19

Abstract: Background and Objectives: The COVID-19 pandemic required rapid adaptation of multidisciplinary tumor board conferences to a virtual setting; however, there are little data describing the benefits and challenges of using such a platform.Methods: An anonymous quality improvement survey was sent to participants of tumor board meetings at a large academic institution. Participants answered questions pertaining to the relative strengths and weaknesses of in-person and virtual settings.Results: A total of 335 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…We discovered a total of 36 papers using our search criteria. The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…We discovered a total of 36 papers using our search criteria. The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was published in 1999 [5]. Most studies had populations from VMDTMs based in the United States of America (n = 10) [5,18,21,25,26,33,35,37,38,46], followed by the United Kingdom (n = 8) [7,17,22,23,43,44,47,48]. The distribution of these studies is described in the S5 File.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations